2010
DOI: 10.1111/j.1439-0434.2010.01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Needle-free Injection Method for Delivery of Bacterial Suspensions into Citrus Leaf Tissues

Abstract: A prototype needle-free device was evaluated for delivery of Xanthomonas citri subsp. citri bacteria into the leaves of cultivars susceptible and resistant to citrus canker. The device delivered a precisely controlled volume of bacterial suspension through infiltration of stomata by injection with pressurized gas. The device produced a uniform inoculation of bacteria into the leaves as measured by the volume of infiltration and diameter of the infiltrated area. No damage to the leaves was observed after inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
1
6
0
2
Order By: Relevance
“…Injection infiltration resulted in the maximum citrus canker incidence among all techniques used in the study because injection with pressurised gas delivered an accurately controlled volume of the Xac suspension through infiltration of stomata and this method produces stomatal form inoculation of bacteria into the leaves and higher number of lesions developed as compared to other techniques. These results were in accordance with Francis et al (2011) who reported that maximum disease was generated through injection infiltration technique in citrus plants. Spray inoculation remained second in the generation of citrus canker disease because the plants were sprayed in the early morning when stomata are potentially open and maximum inoculum was transferred.…”
Section: Discussionsupporting
confidence: 95%
“…Injection infiltration resulted in the maximum citrus canker incidence among all techniques used in the study because injection with pressurised gas delivered an accurately controlled volume of the Xac suspension through infiltration of stomata and this method produces stomatal form inoculation of bacteria into the leaves and higher number of lesions developed as compared to other techniques. These results were in accordance with Francis et al (2011) who reported that maximum disease was generated through injection infiltration technique in citrus plants. Spray inoculation remained second in the generation of citrus canker disease because the plants were sprayed in the early morning when stomata are potentially open and maximum inoculum was transferred.…”
Section: Discussionsupporting
confidence: 95%
“…As previously demonstrated for citrus leaves (Francis et al. ), the needle‐free injector adjusted to pressures required to infiltrate stomates in the fruit rind without wounding (750–790 kPa/cm) was effective for inoculation of fruit to produce lesions of reproducible size and population of Xcc. This inoculation procedure permitted sampling of lesions of uniform size on fruit of known age.…”
Section: Discussionmentioning
confidence: 60%
“…A portable pulse needle‐free injector (Francis et al. ) was used to provide dose‐accurate injections. The nozzle on the injector was modified to ensure uniform contact between the nozzle face and the fruit surface.…”
Section: Methodsmentioning
confidence: 99%
“…; Francis et al. ). Injection–infiltration bioassay and culture methods have certain advantages over PCR‐based or immunological methods, and injection–infiltration bioassay has been considered an accepted standard in some studies (Graham and Leite ; Gottwald et al.…”
Section: Introductionmentioning
confidence: 99%
“…PCR-based methods are important for the detection and quantification of Xcc for regulatory purposes and for research. Both injection-infiltration bioassay and culture of the bacteria are valuable methods for detection and quantification of Xcc in different laboratories and remain appropriate for many studies (Gottwald et al 2009;Bock et al 2010;Francis et al 2011). Injection-infiltration bioassay and culture methods have certain advantages over PCR-based or immunological methods, and injection-infiltration bioassay has been considered an accepted standard in some studies (Graham and Leite 2004;Gottwald et al 2009) due to perceived accuracy of detecting the most important proportion of the population, that is, those that are viable and pathogenic.…”
Section: Introductionmentioning
confidence: 99%